Newly found Tonian metamorphism in Akebono Rock, eastern Dronning Maud Land, East Antarctica - Baba, Sotaro (Elsevier Inc., 2022)
In this paper, we report a new metamorphic age for kyanite-bearing garnet-biotite gneiss collected from Akebono Rock, which is located on Prince Olav Coast, in the Lützow-Holm Complex (LHC), East Antarctica. The metamorphic P–T path estimated from pseudosection modeling, together with garnet compositional zoning and experimentally calibrated geothermobarometry, suggests that the gneiss underwent a clockwise amphibolite-facies P–T history. Two populations of U–Pb zircon ages of 1121–1014 Ma and 972–904 Ma (n = 65) were identified, with the latter population having a weighted mean age of 937 ± 6 Ma. The younger population was dated from overgrowth rims and single zircon grains interpreted as metamorphic in origin. Ti-in-zircon thermometry supports crystallization of these zircon domains and grains at a temperature close to the metamorphic peak of 642 °C at 937 Ma. Monazite EMP dating from the other four samples show an age between 977 and 917 Ma. These lines of evidence indicate that prograde metamorphism of the Akebono Rock gneiss occurred during the Tonian, that is, substantially earlier than the LHC regional metamorphic age of late Neoproterozoic to Cambrian. Our results indicate that a fundamental revision of the sequence of metamorphic events in the Prince Olav Coast area of the LHC is required. We also identified three possible relationships between Akebono Rock and other geological units that record Tonian metamorphism, although we cannot determine which relationship is most likely. In particular, linear magnetic anomalies were identified near the boundary between the LHC and the Western Rayner Complex/inland nunataks of western Enderby Land, suggesting the presence of geological discontinuities. © 2021 International Association for Gondwana Research